Synthesis and characterization of conducting polyaniline-coated cadmium sulphide nanocomposites in reverse microemulsion - Khiew, P.S.; Huang, N.M.; Radiman, S.; Ahmad, M.S. (2004)
II-VI group of semiconductor cadmium sulphide (CdS) nanocrystalline, which were coated with conducting polyaniline (PANI), have been prepared by microemulsion processing technique. The synthesized polyaniline-coated CdS nanocomposites were characterized by UV-Vis absorption spectroscopy, energy filter transmission electron microscopy (EFTEM), FTIR spectroscopy and TGA analysis. The UV-Vis spectrums revealed the enhancement of doping level for the nanocomposites, which is assigned to the existence of greater number of charges on the polymer backbone. The FTIR spectra indicated that the polymers were highly doped and existed in conducting emeraldine salt form. The as-prepared PANI/CdS nanocomposites were polydispersed and have an average size of ca. 17.8 nm. The obtained CdS/PANI nanocomposites showed significant improvement in the thermal behavior as indicated in the TGA thermograph. Â© 2003 Elsevier B.V. All rights reserved.